LSP-TEOC.Pro project (Language for Specific Purposes Teacher Education Online Course for Professional Development) – A step towards the professional development of language teachers. Post-conference issue - Nause, Nicolas (Glottodidactica, 2025)
The article introduces the LSP-TEOC.Pro project (Language for Specific Purposes Teacher Education Online Course for Professional Development, https://lsp-teoc-pro.de/) as presented in this post-conference issue of Glottodidactica. Its first part discusses the project including its rationale, consortium, approach and project phases as well as its main result, the developed self-directed online course. In the second part, an overview of the different contributions collected in this special issue is given.